Fall Risk and Related Factors in Systemic Lupus Erythematosus - Meltem ALKAN MELİKOĞLU,; Fatih BAĞCIER, (Archives of Rheumatology, 2017)
Objectives: This study aims to determine the fall risk in systemic lupus erythematosus (SLE) patients with an objective computerized technique and to evaluate the potential related risk factors for falls in these patients. Patients and methods: A total of 48 female patients (mean age 37.8±12.6 years; range 18 to 65 years) with SLE and 30 female controls (mean age 39.1±15.7 years; range 19 to 66 years) were included. Age, disease duration, anamnesis of falls, fear of falling, and drugs used were recorded. Disease activity (measured with SLE disease activity index Safety of Estrogens in Lupus Erythematosus National Assessment modification) and damage (measured with Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index) were evaluated. For the evaluation of fall efficacy, we used the Falls Efficacy Scale International. Fall risk analysis was performed by using a computerized posturography device. Results: Seven patients (15%) had anamnesis of falls during the last 12 months, whereas only one control (3%) had this anamnesis (p=0.042). Fear of falling was reported by 40% of the patients and 30% of the controls (p=0.042). Falls Efficacy Scale International scores were found to be higher in patients than in controls (p=0.042). With the computerized system used, higher fall risk results were recorded in patients than in controls (59.3±29.5 and 35.8±26.9, respectively; p<0.001). Low, moderate, and high fall risks were recorded as 31%, 15%, and 54% in the patients, respectively, and as 53%, 23%, and 23% in the controls, respectively. Low, moderate and high fall risk distribution was also worse in patients than in the controls (p=0.030). No significant correlation was found between fall risk and the other factors evaluated, except Falls Efficacy Scale International, which was significantly correlated with both fall risk assessment and fall risk category in the patients (r=0.311, p=0.031). Conclusion: Fall risk was found to be higher in SLE patients than in controls. The higher fall risk in these patients seems to be affected by the disease itself rather than its other characteristics. Future studies investigating the possible coexisting balance problems in SLE may contribute to the management of the disease.